Current Concepts in the Management of Obstetrical Brachial Plexus Injuries: The Taipei Experience - Chuang, David Chwei-Chin (Thieme Medical Publishers, 2004)
Excluding patients in the early period before 1992 because of immaturity and patients after 2000 because the follow-up period is not long enough, we collected and operated for 78 patients with an initial obstetrical brachial plexus operation during the period of infancy with an average age of 4.9 months (range, 3–9 months). Another 10 patients were operated beyond the period of infancy, with an average age of 19.2 months (range, 12–30 months). The results show that, when indicated, surgical treatment is still more valuable than conservation in both ruptured and avulsed cases. Some conclusions are drawn. An initial obstetrical brachial plexus palsy with no elbow flexion but good hand function is not an urgent indication for early exploration. However, an obstetrical brachial plexus palsy with total hand palsy is an urgent indication requiring early nerve surgery within 3 months. Nerve grafts for ruptured cases should be as short and numerous as possible. Direction of nerve grafts to the planned target nerves yielded better results than the cable nerve grafts randomly, achieving less aberrant reinnervation between shoulder and elbow. Nerve transfers should be applied often in avulsed cases, including intraplexus and extraplexus transfers. Nerve transfer has the further advantage of minimizing the aberrant reinnervation between shoulder and elbow.